Revisiting demographic processes in cattle with genome-wide population genetic analysis - Orozco-terWengel, Pablo; Barbato, Mario; Nicolazzi, Ezequiel; Biscarini, Filippo; Milanesi, Marco; Davies, Wyn; Williams, Don; Stella, Alessandra; Ajmone-Marsan, Paolo; Bruford, Michael W. (Frontiers in Genetics, 2015)
The domestication of the aurochs took place approximately 10,000 years ago giving rise to the two main types of domestic cattle known today, taurine (Bos taurus) domesticated somewhere on or near the Fertile Crescent, and indicine (B. indicus) domesticated in the Indus Valley. However, although cattle have historically played a prominent role in human society the exact origin of many extant breeds is not well known. Here we used a combination of medium and high-density Illumina Bovine SNP arrays (i.e. ~54,000 and ~770,000 SNPs respectively), genotyped for over 1,300 animals representing 56 cattle breeds, to describe the relationships among major European cattle breeds and detect patterns of admixture among them. Our results suggest modern cross-breeding and ancient hybridisation events have both played an important role, including with animals of indicine origin. We use these data to identify signatures of selection reflecting both domestication (hypothesised to produce a common signature across breeds) and local adaptation (predicted to exhibit a signature of selection unique to a single breed or group of related breeds with a common history) to uncover additional demographic complexity of modern European cattle.